Collaboration and Learning Processes in Value Co-Creation: A Destination Perspective. (March 2023) - Melis, Giuseppe; McCabe, Scott; Atzeni, Marcello; Del Chiappa, Giacomo
Value co-creation has emerged as an important competitive strategy leading to value innovation. In tourist destinations co-creation results from the participation of multiple actors synchronously and contextually in value realization. Yet value co-creation remains highly theoretical and lacks empirical operationalization, especially in destination contexts. Are tourism destinations able and sufficiently mobilized to exploit the potential offered by co-creation theory? This paper operationalizes two fundamental dimensions of the value co-creation process, collaboration and learning, by developing and testing a measurement scale to evaluate the perceived impact of these dimensions on the market performance of actors at a tourist destination. Contributions to the literature on value co-creation and learning as well as managerial implications are discussed and suggestions for further research are made.